2018
DOI: 10.1080/01596306.2018.1451304
|View full text |Cite
|
Sign up to set email alerts
|

‘What is puberty, then?’ Smartphones and Tumblr images as de/re-territorialisations in an upper secondary school classroom

Abstract: In this paper we seek an understanding of the part mobile phone use plays in the capitalist assemblages present in school classrooms. Capitalism is approached in the vein of Gilles Deleuze's and Félix Guattari's Anti-Oedipus, through the continuous movement of de-and re-territorialisation. The empirical grounding is a wide study on mobile phone use conducted at an upper secondary school in Finland. A particular focus of this paper is one psychology lesson on puberty and the highlighting of ways in which territ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 19 publications
(13 reference statements)
0
5
0
Order By: Relevance
“…Google, Microsoft) via applications, and the current capitalist economy – it produces students as a workforce for digital labour in classrooms. Students take part in the production of data that can be monetized by private companies when using their mobile devices in class, working on assignments and searching for information on the Internet (Paakkari and Rautio, 2019). The concept of assemblage has proved a particularly useful tool for analysing complex and entangled phenomena where several factors affect each other, and straightforward causal relations lose their explanatory power.…”
Section: Activity-tracking Technologies As Assemblagesmentioning
confidence: 99%
“…Google, Microsoft) via applications, and the current capitalist economy – it produces students as a workforce for digital labour in classrooms. Students take part in the production of data that can be monetized by private companies when using their mobile devices in class, working on assignments and searching for information on the Internet (Paakkari and Rautio, 2019). The concept of assemblage has proved a particularly useful tool for analysing complex and entangled phenomena where several factors affect each other, and straightforward causal relations lose their explanatory power.…”
Section: Activity-tracking Technologies As Assemblagesmentioning
confidence: 99%
“…Whilst several register questionnaires in Finland, for example, have suggested that young people, especially girls, experience sexual or gender-based harassment regularly, they also suggest that most of the cases do not take place inside schools (Ikonen & Helakorpi, 2019). The spaces and places of the school have become more blurred, however, due to the presence of mobile phones (Paakkari & Rautio, 2019). This means new possibilities for sexual and gender-based harassment which is even more difficult for teachers to see (Rivers, 2013;Boyd, 2014).…”
Section: New Research Widens the Scopementioning
confidence: 99%
“…children’s hands holding objects in literacy practices, as part of a Baradian phenomenon that includes the exploitative mining of minerals, such as coltan from Congo, global production lines and capitalist desires (cf. Fuchs, 2014; Paakkari and Rautio, 2018) (see Figure 1).…”
Section: Unruly Encountermentioning
confidence: 99%